Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan PT. Angkasa Pura II Periode 2019 – 2023 - Hengki Hengki; Jamaludin Jamaludin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - This study aims to assess the financial performance of PT. Angkasa Pura II during the 2019–2023 period through a comprehensive financial ratio analysis, including liquidity, profitability, solvency, and activity ratios. The research population encompasses all of the company's annual financial statements, with the specific sample consisting of audited financial reports from 2019 to 2023. The methodology employs a descriptive quantitative approach, utilizing ratio calculation techniques to capture annual financial trends and conditions, which are subsequently compared against relevant industry standards. The results reveal that the financial performance of PT. Angkasa Pura II experienced sharp fluctuations, with most indicators failing to meet industry benchmarks. Profitability ratios (NPM, ROA, ROE) showed positive performance in 2019 but plummeted drastically in 2020 and 2021 due to the impact of the COVID-19 pandemic. Despite improving in 2022 and 2023, the five-year average remains categorized as unhealthy as it falls significantly below standard. Liquidity ratios (Current Ratio and Quick Ratio) were also categorized as less than healthy despite a recovery late in the observation period, while the Cash Ratio performed relatively better, albeit fluctuating. Regarding solvency, the DAR and DER ratios increased steadily until 2022, indicating a high dependency on debt and resulting in an unhealthy categorization. Meanwhile, activity ratios showed mixed results: Receivable Turnover and Inventory Turnover were categorized as healthy, yet Total Asset Turnover and Fixed Asset Turnover remained less than healthy. Overall, despite recovery signals in 2022–2023, the company's general financial performance is still considered less than healthy, necessitating further strategic improvements in profitability, liquidity, and asset utilization efficiency.